Evaluation of Arabic Language Teaching Skills of Student Interns at MAN 1 Surakarta from the Perspective of Mentoring Teachers - Ngatmin Abbas; Slamet Budiyono; Siti Nurjanah; Ramadhan Ramadhan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This research aims to evaluate the teaching skills of twelve students undergoing Field Experience Practice (PPL) in the Islamic Education Program at MAN 1 Surakarta, with a focus on two students teaching Arabic in twelfth-grade classes. The research method used is qualitative descriptive, with a population involving twelve PPL students at MAN 1 Surakarta. The study, conducted for one month, analyzes aspects of personality, written preparation, and the implementation of teaching practice.The results show that both PPL students successfully achieved a high level of teaching skills, aligning with the program's goal to produce professional Islamic Education teachers. The mentor teacher's assessment for the two students was 88, 87, and 86, respectively. Nevertheless, their achievements remained good with total scores of 89, 88, and 87. The conclusion of this research provides a holistic overview of the students' readiness to face real-world challenges in teaching Arabic. This study contributes to understanding the effectiveness of the field practice approach in developing teaching skills for PPL students in the context of Arabic language instruction.